الخطــــر الجـــــوي أساســاً لمسؤوليــة ناقــل الأشخاص جــــوَّاً - سليمان الأحمد, محمد; مسلم يونس, هادي (revue mofakir, 2018)
أضحى النقل أداة متجددة الأهمية عبر جميع المراحل التي مر بها ، والنقل اما أن يكون براً أو عبر الجو ، وهو في كل هذه الصور اما أن يكون لغرض نقل الأشياء أو نقل الأشخاص ، ولأرتباط النقل الجوي بواسطة محددة تتكفل تلبية هذه الحاجة الملحة للأشخاص ، وهي الطائرة ، فقد أنصب اهتمام الأتفاقيات الدولية والتشريعات الداخلية على تنظيم جانبين مهمين يتصلان بهذه الصورة المهمة للنقل : أولاهما : جانب يتعلق بنظم الملاحة الجوية ووضع القواعد التي تكفل مؤسسة قطاع الطيران المدني الدولي ، لأتاحة الحرية لهذا الطيران في التحليق فوق فضاءات جميع الدول ، وما شاكل من قواعد متصلة بهذا القطاع ، أمـّـا الجانب الآخر ، فهو متعلق بتنظيم العلاقة القائمة بين الناقل الجوي الذي يتخذ في العادة صيغة الشركات أو هيئات متخصصة بهذا الغرض ، والطرف المستفيد التي تتحقق مصلحته في النقل ، هو اما الشاحن للبضاعة في النقل الجوي للأشياء ، وعادة ما يكون تاجراً ، أو المسافر في النقل الجوي للأشخاص ، وعادة ما يكون مستهلكاً ، ولأختلاف العلاقتين عن بعضهما ، يجب أن يكون الأحكام المتعلقة بكل علاقة مختلفة كذلك ، فالنقل الجوي للأشخاص يرتبط بنقل أناس لا تقارن قيمهم بقيمة البضائع المنقولة ، كما أن مسؤولية الناقل الجوي للأشخاص يجب أن تكون أشد من مسؤوليته وهو ينقل أشياءاً ، وعلى الرغم من أن اتفاقية وارشو لعام 1929 ، تضمنت قواعد خففت كثيراً من مسؤولية الناقل الجوي ، نظراً للمبررات التي كانت سائدة حينها والتي كانت تفقق في حالة الطيران المدني في ذلك الوقت ، فقد كانت الطائرات أقل أماناً ، ولم تكن هناك نظم متطورة للتأمين ، كما أن المستعملين لقطاع الطيران كانوا أقل ، وبالتالي فأن الأرباح التي يمكن أن تجنيها شركات الطيران قد لا تستوعب نفقات أي حادث جوي ، لكن المسألة سرعان ما تغيرت بتغير حال الطيران المدني واشباع نشاطه واقبال الجمهور عليه واتساع رقعة التأمين وأنماطه ، واعتماده على طائرات مستحدثة أكثر أماناً وجودة ، مما أدى الى التغيير في الأحكام المتعلقة بمسؤولية الناقل الجوي عموماً ، والناقل الجوي للأشخاص خصوصاً . وعلى الرغم من أن اتفاقات مونتريال المتلاحقة الى نسختها الأخيرة عام 1999 ، قد شددت من مسؤولية الناقل الجوي ، الا أنه في تصورنا مازال الأمر بحاجة الى مزيد من التشدد ، احتراماً لكرامة الأنسان وتعزيز الثقة في قطاع الطيران ودعم النقل الجوي للأشخاص ، وكل هذا لا يستقيم الا اذا جعلنا الأساس الجديد لمسؤولية الناقل الجوي للأشخاص يكتمن في الخطر الجوي .   Summary  : Has become a transportation tool renewed interest across all stages experienced by , and transportation to either be by land or by air , which is in all of these types either be for the purpose of the transfer of goods or the transport of persons , and the correlation of air transport by specific tool ensure to satisfy this urgent need for people , which is an aircraft , has focused the attention of international agreements and domestic legislation on the regulation of two important aspects relate to this , is the job of the transfer : the first : by the systems of air navigation and to develop rules to ensure that the enterprise sector , the international civil aviation , to allow freedom for this flight in flight over the spaces of all states , and the like of the rules connected to this sector , the other aspect , it is related to the regulating of the relationship between the air carrier which takes usually a formula of companies or entities are specialized for this purpose , and beneficiary party which realized his interest in transportation is either the shier of the goods in air transportation of things , and is usually a merchant , or the traveler in the air transport of persons , and is usually a consumer ,but a difference relationships for each other , must be provisions for each relationship different also, air transportation for persons associated with the transfer people who do not compare the values of the value of goods transported , and the liability of the carrier air for people to be more than his liability when he transferred things , although the( WARSAW) convention on year 1929 included rules eased much of the liability of the air carrier ,due to the reasons that prevailed then , which was realized in the case of civil aviation at that time , the aircrafts were less safe , and there were no sophisticated systems for the insurance , and the users of the aviation sector were less ,thus the profits that can accrue to the airline companies may not absorb the expenses of any incident air , but the issue quickly changed climate event of civil aviation and to satiate its activity and the publics demand to it and the expansion of insurance and patterns , and its dependence on innovative aircraft more safer and quality , which led to the change in the in the provisions on the liability of the air carrier in general and air carrier for people in particular . In spite of the agreements( MONTREAL) subsequent to the latest version in 1999 ,had emphasized the liability of the air carrier , except that in our perception still is needed to more stresses as the respect for human dignity and promote confidence in the aviation sector and to support the air transport of persons , and all this is to be correct , only when we made the air risk the base of the new persons air carrier , s liability .